Integrated and streamlined microfluidic device for molecular diagnosis of pathogen through direct PCR amplification - Dohwan Lee; Tae Seok Seo (Heliyon)
Background: Polymerase chain reaction (PCR) is a gold-standard method widely acknowledged for offering precise and rapid analysis of genetic material, particularly having a crucial role in detecting pathogens and diagnosing infectious diseases. However, the complexity of the PCR process (including nucleic acid extraction/purification, amplification, and amplicon detection) hinders its widespread adoption in point-of-care testing, where simplicity and rapidity are essential for practical use. Results: In this study, we developed a microfluidic genetic analysis device that leverages direct PCR technology to simplify the entire PCR process, focusing on enhancing the usability and accessibility of the device for point-of-care diagnostics. Direct PCR, which enables direct DNA amplification from biological samples without the need for DNA extraction and purification, streamlines the device architecture and transforms it into a more user-friendly form. Within the device, two spatially separated zones for PCR and micro-capillary electrophoresis (μCE) are sequentially connected via a microchamber plate, which is slidable on top of the device and transfers the amplified products from the PCR zone to the μCE zone for subsequent analysis. Using our device, we quantitatively analyzed two types of bacteria—Escherichia coli (E. coli) and Staphylococcus aureus (S. aureus)—in milk (food poisoning simulation) with a sensitivity of up to 10 bacterial cells. Significance: Considering how prominent PCR is for diagnostics, this work represents the potential to make traditionally labor-intensive molecular assays available in a decentralized point-of-care setting.